Comparative Study of Traditional Single-Needle Electrospinning and Novel Spiral-Vane Electrospinning: Influence on the Properties of Poly(caprolactone)/Gelatin Nanofiber Membranes - Xu, Qi; Liu, Wei; Yi, Bingcheng (Frontiers in Bioengineering and Biotechnology, 2022)
Spiral-vane electrospinning (SVE), a novel needleless electrospinning, was proven to be effective in obtaining high-throughput production of nanofibers. However, the properties of the electrospun nanofibers produced by SVE remain relatively underexplored, especially in comparison with that made by traditional single-needle electrospinning (SNE). Hence, for the comparative study between SNE and SVE in this study, the difference in the preparation mechanism was analyzed firstly using numerical simulation, followed by the experimental analysis of the effects of spinneret types on the quality and biocompatibility of electrospun poly(caprolactone)/gelatin (PCL/Gel) nanofibers. The values predicted by the electric field results were consistent with the experimental data, showing that the PCL/Gel nanofibers prepared by SVE have the higher yields compared to that by SNE. Although the different spinnerets (i.e., needle and spiral vane) had little effect on the surface chemistry, thermal stability, and composition of the PCL/Gel nanofibers, it had great effects on their fiber diameter distribution and mechanical properties in which SVE-electrospun nanofibers have the more wider diameter distribution and the higher softness. Furthermore, the SVE-electrospun nanofibers was also proven to exhibit good biocompatibility for cell growth of human adipose-derived stem cells (hADSCs) and cell-fiber interactions. Summarily, compared to the traditional SNE, SVE-electrospun nanofibers exhibited many merits including high-throughput yield, good air permeability, and compliance, which provides a facile and effective platform for the improvement of nanofiber applications in biomedical fields (e.g., tissue engineering, cosmetic, and medical textiles).